Case Report: Euglycemic ketoacidosis in a non-diabetic patient: a rare adverse effect of SGLT2 inhibitor therapy - Prasad, Sai; Sharma, Shreya; Shetty, Rudrakshi; Singh, Snigdha; Parmar, Vidhi; Shivaprasad, Channabasappa; Dhaduk, Vidhi (Frontiers in Endocrinology, 2026)
BackgroundSodium-glucose cotransporter-2 (SGLT2) inhibitors are increasingly prescribed for heart failure and chronic kidney disease, irrespective of diabetic status. While their cardiovascular and renal benefits are well established, euglycemic ketoacidosis (EKA) remains a rare but potentially life-threatening complication that can occur even in non-diabetic individuals.Case presentationWe report a 58-year-old man with ischemic cardiomyopathy (LVEF 35%) and stage 2 chronic kidney disease who developed nausea, vomiting, and fatigue two weeks after initiating dapagliflozin. Laboratory evaluation revealed high-anion-gap metabolic acidosis (pH 7.21 [reference: 7.35–7.45], HCO3- 12 mmol/L [reference: 22–28 mmol/L], anion gap 23 mmol/L [reference: 8–16 mmol/L])with markedly elevated β-hydroxybutyrate (5.4 mmol/L) and normal plasma glucose (108 mg/dL). Diabetes, infection, lactic acidosis, and hepatic dysfunction were excluded.Management & outcomeThe SGLT2 inhibitor was discontinued, and the patient was treated with intravenous saline, insulin infusion, and dextrose. Metabolic parameters normalized within 48 hours, and he was discharged in stable condition. No recurrence was noted at three-month follow-up.ConclusionThis case highlights that SGLT2 inhibitors can precipitate euglycemic ketoacidosis even in non-diabetic patients. Because normal glucose levels may obscure recognition, clinicians should maintain a high index of suspicion and perform ketone testing in patients on SGLT2 therapy who present with unexplained gastrointestinal or constitutional symptoms.